ANALYSIS OF THE INFLUENCE OF DIGITAL TECHNOLOGY, TAX KNOWLEDGE, AND TAX SOCIALIZATION ON TAXPAYER COMPLIANCE IN TAX SERVICE OFFICE PRATAMA PRAYA - RUSDI RUSDI; ELVINA SETIAWATI; Baiq Nurafiza (Program Sarjana Manajemen Universitas Internasional Batam, 2023)
This study aims to empirically examine the Effect Analysis of Digital Technology, Tax Knowledge, and Tax Socialization on Taxpayer Compliance at Tax Service Office Pratama Praya. So that the research variables consist of 3 (three) independent variables,namely Digital Technology (X1), Tax Knowledge (X2), and Tax Socialization (X3) and the dependent variable is Taxpayer Compliance (Y). The population of this study is individual taxpayers who are registered at Tax Service Office Pratama Praya. Samples were taken using a sampling technique that is incidental sampling. This study analyzed questionnaires from primary data derived from the answers of 100 individual taxpayers. Data were analyzed using SPSS 26. The results of this study indicate that Digital Technology has a significant effect on Taxpayer Compliance, Tax Knowledge has no significant effect on Taxpayer Compliance, and Tax Socialization has a significant effect on Taxpayer Compliance. The results of this study also show that the independent variables (Digital Technology, Tax Knowledge, Tax Socialization) are able to explain the dependent variable (Taxpayer Compliance) of 75.8%. While the remaining 24.2% Taxpayer Compliance is influenced by other variables outside this research model.